A review of thermal homogeneous catalytic deoxygenation reactions for valuable products. Issue 2 (February 2020) - Kong, Zhaoni; He, Liang; Shi, Yuzheng; Guan, Qingqing; Ning, Ping
Abstract: To remove high oxygen content is important to make high quality oil and valuable products. In this paper, the research on homogeneous catalytic deoxygenation reactions, including decarboxylation (DCX)/decarbonylation (DCN), hydrodeoxygenation (HDO) is reviewed. Based on DCX/DCN, the classic radical reactions such as the Barton decarboxylation, Henkel, Hunsdiecker and Kochi reactions were introduced, the practice and overall performance are also discussed. In addition, the different reaction pathways and mechanisms were demonstrated and the key chemical processes have been selected from the literature as examples to elaborate the critical emphasis on the mechanistic understanding. The applications of the catalytic deoxygenation reactions for high-value products have also been highlighted. Overall, this review provides insight discussions on the DO issues and progresses in homogeneous catalytic aspects. Abstract : Chemical engineering; Bio-oil; Upgrading; Deoxygenation (DO); Homogeneous catalysis; Catalyst; Bioconversion; Energy sustainability; Fuel technology; Natural product chemistry